In search of excellence in e-customer logistics service - Barbara Ocicka; Marta Raźniewska (International Journal of Management and Economics, 2016)
The e-commerce market has been developing very rapidly and changing traditional distribution systems. The development of online channels is matched by a similar evolution of companies' logistics systems. As a consequence, logistics processes management now significantly influences e-customer service quality, which has emerged as a competitive advantage. The main goal of this paper is to identify e-commerce business models, modern distribution channels and management tools that would facilitate a continuous improvement in e-customer logistics service. Based on the literature and interviews with e-commerce services providers, we provide a plethora of good and best practices useful for managers in the rapidly developing and highly competitive e-commerce business.
Keywords: L21; L81; M15; 650; e-customer logistics service; multi- and omnichannel distribution; cooperation on the e-market